Implementation of Knowledge Management to Support Strategic Decision-Making in Property Development Companies - Kusumastuti, Yuliwanda Anggi; Akbar, Tsabita Hanifah; Raharja, Muhammad Ridwan Ali; Sugiarti, Yuni (JESII: Journal of Elektronik Sistem InformasI, 2024)
The property industry faces challenges in managing knowledge dispersed across various departments, hindering efficiency and decision-making. To address this issue, the aim of this research is to develop Knowledge Management (KM) using the Rapid Application Development (RAD) method, which enables rapid and responsive system development according to organizational needs. By utilizing the SECI model to manage tacit and explicit knowledge, this KM prototype is capable of addressing knowledge fragmentation, improving information management efficiency, and supporting data-driven decision-making. The research findings show that this system also facilitates knowledge transfer between departments and enhances collaboration, providing a foundation for KM implementation that can increase competitiveness in the property industry.